Blood Vessel Extraction and Optic Disk Localization for Diabetic Retinopathy - Kanjanasurat, Isoon; Purahong, Boonchana; Pintavirooj, Chuchart; Satayarak, Nitjaree; Benjangkaprasert, Chawalit (My University, 2020)
This paper presents methods of vascular extraction and optic disk localization in the retinal images. Our approach begins with preprocessing to improve the quality of blood vessels. In the next step, a matrix filter was applied to express blood vessels. Finally, the blood vessel structure was used to estimate the location of the optic disk. The proposed method was tested on all different forty retinal images from the DRIVE database, which public retinal image dataset. The results of vessel extraction were compared with the ground truth image. The error of vascular extraction showed that the average sensitivity and accuracy were 79.81% and 94.98%, respectively. The optic disk localization achieved 97.5%.
Keywords: Blood vessel extraction; Diabetic retinopathy; Fundus image; Optic disk localization